(untitled) (TSUL LEGAL REPORT, 2026)
This scientific article provides a comprehensive constitutional and legal analysis of the organizational and legal forms of non-governmental non-profit organizations (NGOs). NGOs are considered as an important institution that enables citizens to express their interests, actively participate in social processes, and directly influence the system of public administration in modern society. Therefore, the issue of defining their legal status, organizational and legal forms, and mechanisms of activity on a constitutional basis is of particular relevance. The article first reveals the concept of NGOs and their legal characteristics. The constitutional right of citizens to freedom of association is examined, and the role of NGOs as one of the main forms of exercising this right is substantiated. Various organizational and legal forms defined in national legislation – public associations, foundations, institutions, unions, and other structures – are analyzed in terms of their legal status, procedures of establishment, mechanisms of activity, control, and state support. Furthermore, the experience of foreign countries is studied and compared with the practice of Uzbekistan. In this process, the constitutional and legal status of NGOs in democratic states, mechanisms of cooperation with the state, and their role in the development of civil society are comparatively analyzed.